Thermodynamic Performance Analysis of a Triple-loop Air-source Heat-pump Heat Recovery System - Ma Anna; Ma Guoyuan; Wang Lei; Zhou Feng; Jiang Mingjian; Yan Xianghui (Zhileng xuebao)
To improve the performance of an air-source heat pump system under large temperature difference conditions, this paper proposed a triple-loop air-source heat pump system scheme. An energy recovery performance test platform was set up according to the exhaust energy recovery in a public building air-conditioning system. The performances of the single- and triple-loop heat-pump systems were tested through experiments under different outdoor-temperature conditions in winter and summer. The results show that the overall performance of the triple-loop system was significantly higher than that of the single-loop system under all operating conditions. With the increase in the indoor and outdoor temperature difference, the triple-loop heat pump system could significantly minimize the problems of excessive compression ratio and system performance degradation of the traditional air-source heat pump. Under winter conditions, the increase rate of the coefficient of performance (COP) of the triple-loop system reached up to 1.88. When the indoor and outdoor temperature difference was 40 ℃, the COP of the triple-loop system was 54.8% higher than that of the single-loop system. Under summer conditions, the increase rate of the COP of the triple-loop system reached 89.8%. When the indoor and outdoor temperature difference was 13 ℃, the COP of the triple-loop system was 74.6% higher than that of the single-loop system.